A method for forming a composite passivation film and a chip containing the passivation film

Through the composite passivation film formation method, the problem of poor density and stability of the passivation film on the surface of GaN material is solved, and efficient ZnS film formation is achieved, which improves the reliability and device performance of the chip.

CN118969641BActive Publication Date: 2024-12-20HANGZHOU XIANTUO ELECTRONIC TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411469353.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2024-12-20
Estimated Expiration
2044-10-21

AI Technical Summary

Technical Problem

Gallium nitride (GaN) materials face lattice stress problems in surface passivation, resulting in poor density and stability of the passivation film, affecting device reliability.

Method used

The composite passivation film formation method is adopted, including pretreatment of semiconductor wafers, magnetron sputtering ZnS passivation film, H2S and nitrogen plasma treatment, and sulfur hexafluoride atmosphere assisted annealing to form a dense, stable and low leakage passivation film. .

Benefits of technology

It significantly improves the reliability of the chip, enhances the crystallinity and uniformity of the ZnS film, reduces film defects and stress, and improves the device's resistance to voltage and low leakage characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118969641B_ABST
    Figure CN118969641B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of chip passivation, and in particular to a method for forming a composite passivation film and a chip containing the passivation film. The method comprises the following steps: pretreatment of the surface of a semiconductor wafer; magnetron sputtering and plasma treatment of a ZnS passivation film; and annealing of a passivation wafer assisted by a sulfur hexafluoride atmosphere. The present invention performs mixed gas plasma treatment of H2S and nitrogen on the surface of a coated wafer. The H2S cluster ions generated by the mixed gas plasma of H2S and nitrogen provide abundant S ions, fill S ions at S vacancies in a ZnS film, passivate S dangling bonds, thereby reducing defects and stress of the film, improving the crystallinity of the ZnS film, and enhancing the stability and uniform density of the film. In addition, H ions can adjust the charge distribution on the surface of the film, further promoting the filling and passivation effect of S ions, avoiding the problems of microcracks, microdefects, and film layer peeling in the passivation film, and improving the reliability of the chip.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of chip passivation, and in particular to a method for forming a composite passivation film and a chip comprising the passivation film. Background Art

[0002] Gallium nitride (GaN) is a semiconductor material with a wide bandgap, high electron mobility and excellent thermal conductivity. It has been widely used in high-power, high-frequency electronic devices and optoelectronic devices. In order to improve the performance of GaN devices, surface passivation technology has become a research focus. Passivation technology covers the GaN surface with a protective dielectric film to keep the surface of the semiconductor in a stable state. It can also effectively prevent semiconductor surface contamination and improve the electronic performance and thermal stability of the material.

[0003] Traditional silicon semiconductors can often use lattice atoms to form a passivation film, which reacts with oxygen through a gas phase method to form a dense silicon dioxide passivation film. This passivation film matches the lattice structure of silicon well, can effectively reduce surface defects, suppress dangling bonds in the electronic state, and improve the performance and stability of the device. However, GaN materials face great challenges in surface passivation. Although gallium nitride will naturally form oxides when exposed to air, what is formed is a gallium oxide (Ga2O3) film. Gallium oxide has five isomers, among which the most stable β-Ga2O3 has a monoclinic structure. This structure does not match the lattice structure of GaN, resulting in large lattice stress during passivation, making it difficult to form a stable and efficient passivation layer.

[0004] Therefore, GaN cannot directly form an effective native passivation film through lattice atoms, but needs to passivate its surface through external sputtering deposition of other materials to reduce surface defects and improve device performance. However, the passivation film formed by deposition is easily affected by power, chamber pressure and gas flow during the deposition process, which leads to the formation of cluster particles with more defects in the passivation film, seriously affecting the density and stability of the passivation film, and reducing the reliability of the semiconductor material. Summary of the invention

[0005] In order to solve the above technical defects, the present invention has developed a method for forming a composite passivation film and a chip comprising the passivation film. The formed passivation film has excellent density, stability and low leakage characteristics, and its application on the chip can greatly improve the reliability of the chip.

[0006] A method for forming a composite passivation film comprises the following steps:

[0007] S1: Pretreatment of semiconductor wafer surface

[0008] The GaN semiconductor wafer is sequentially immersed in an acetone solution, an isopropanol solution and an HF solution for ultrasonic cleaning, and is rinsed with deionized water after each ultrasonic cleaning. After drying with nitrogen, a clean wafer is obtained, and the clean wafer is placed in a closed steam heating reactor, and α-pinene is heated by a constant temperature heating table to evaporate in the steam heating reactor. After the α-pinene is completely evaporated, the temperature in the reactor is maintained to obtain a surface pre-treated wafer, and the surface pre-treated wafer is taken out and placed under a nitrogen flow for cooling, and then immediately transferred to a sputtering chamber of a magnetron sputtering instrument to prepare for magnetron sputtering;

[0009] S2: Magnetron sputtering and plasma treatment of ZnS passivation film

[0010] The ZnS target material is installed on the target position of a magnetron sputtering instrument, a surface pre-treated wafer is installed in the sputtering chamber of the magnetron sputtering instrument, Ar gas is introduced, a ZnS passivation film is plated on the surface of the surface pre-treated wafer, and a coated wafer is obtained, then the Ar gas is changed to a mixed gas of H2S and nitrogen, the working gas pressure and the gas flow rate of the mixed gas of H2S and nitrogen are adjusted, and the magnetron sputtering instrument is started to perform a mixed gas plasma treatment of H2S and nitrogen on the surface of the coated wafer to obtain a passivated wafer;

[0011] S3: Sulfur hexafluoride atmosphere assisted passivation wafer annealing

[0012] Place the passivated wafer in an annealing furnace, exhaust the gas with nitrogen first, then introduce sulfur hexafluoride gas, control the flow rate of sulfur hexafluoride gas, slowly increase the temperature and maintain the temperature and gas flow rate for annealing to obtain an annealed wafer. After the annealing is completed, stop the sulfur hexafluoride gas supply, exhaust the gas with nitrogen, discharge the residual gas in the furnace and ensure that the waste gas passes through the exhaust purification system, then take out the annealed wafer and store it in a dry environment.

[0013] Furthermore, step S1 of pre-treating the surface of the semiconductor wafer comprises the following steps:

[0014] S1.1: Immerse the GaN semiconductor wafer in an acetone solution, then place it in an ultrasonic cleaning machine, perform ultrasonic cleaning at an ultrasonic frequency of 20-25kHz for 8-10 minutes, take it out and rinse it with deionized water for 2-3 times, then immerse it in an isopropanol solution, perform ultrasonic cleaning at an ultrasonic frequency of 20-25kHz for 8-10 minutes, take it out and continue to rinse it with deionized water for 2-3 times, then immerse it in a HF solution with a concentration of 25-30% and perform ultrasonic cleaning at an ultrasonic frequency of 15-20kHz for 2-2.5 minutes, take it out and rinse it with deionized water for 4-5 times, blow it dry with nitrogen to obtain a clean wafer;

[0015] S1.2: Place the clean wafer on the sample rack of the steam-heated reactor, place α-pinene on a constant temperature heating table, and then introduce nitrogen into the steam-heated reactor so that the nitrogen content accounts for 85-90% of the gas content in the steam-heated reactor, and the rest is air. After sealing the steam-heated reactor, start the vacuum pump to evacuate the air pressure in the reactor to 400-500Torr, and heat the temperature in the reactor to 80-85°C. Then start the constant temperature heating table to heat α-pinene to 85-90°C. After all the α-pinene in the constant temperature heating table is evaporated, turn off the constant temperature heating table and maintain the temperature in the reactor for 10-15 minutes, then turn off the heating device to obtain a surface pretreated wafer, take out the surface pretreated wafer, cool it to room temperature under a nitrogen flow, and then immediately transfer it to the sputtering chamber of the magnetron sputtering instrument to prepare for magnetron sputtering.

[0016] Furthermore, the magnetron sputtering and plasma treatment of the ZnS passivation film in step S2 includes the following steps:

[0017] S2.1: Install the ZnS target material on the target position of the magnetron sputtering instrument. The surface pre-treated wafer prepared in step S1.2 is installed in the sputtering chamber of the magnetron sputtering instrument. The sputtering chamber is evacuated to a vacuum with the vacuum degree controlled at 10 -5 -10 -4 Pa, then introduce Ar gas with a purity greater than 99.999%, adjust the working gas pressure to 0.5-1Pa, set the Ar gas flow rate to 25-30sccm, then start the magnetron sputtering instrument, set the RF power to 150-200W for magnetron sputtering, and plate a ZnS passivation film on the surface of the surface pretreated wafer, and control the thickness of the ZnS passivation film to be 300-500nm to obtain a coated wafer;

[0018] S2.2: Adjust the vacuum degree in the sputtering chamber of the magnetron sputtering instrument to 2×10 -3 -8×10 -3 Pa, the introduction of Ar gas is changed to the introduction of a mixed gas of H2S and nitrogen, the working gas pressure is adjusted to 3-5Pa, the gas flow rate of the mixed gas of H2S and nitrogen is adjusted to 10-15sccm, the magnetron sputtering instrument is started, the RF power is set to 80-100W, and the surface of the coated wafer is treated with a mixed gas plasma of H2S and nitrogen for 4-5 minutes to obtain a passivated wafer.

[0019] Further, step S3, sulfur hexafluoride atmosphere assisted passivation wafer annealing, comprises the following steps:

[0020] S3.1: Place the passivated wafer in an annealing furnace, which is connected to an exhaust purification system. First, exhaust the gas with nitrogen for 6-8 minutes, then introduce sulfur hexafluoride gas, control the sulfur hexafluoride gas flow rate to 10-30 sccm, control the heating rate in the annealing furnace to 8-10°C / min, slowly heat to 280-300°C, and then maintain the temperature and gas flow rate for 45-60 minutes to obtain an annealed wafer;

[0021] S3.2: After the annealing is completed, stop the sulfur hexafluoride gas supply, exhaust with nitrogen for 10-15 minutes, discharge the residual gas in the furnace and ensure that the exhaust gas passes through the exhaust purification system, then take out the annealed wafer and store it in a dry environment.

[0022] Furthermore, the steam-heated reactor in step S1.2 is internally equipped with a sample rack and a constant temperature heating table, the sample rack is arranged in a double-bar configuration, and the wall of the steam-heated reactor is connected to a vacuum pump.

[0023] Furthermore, the amount of α-pinene added in step S1.2 is 1 / 20-1 / 15 of the volume of the steam-heated reactor.

[0024] Furthermore, in step S2.1, the purity of the ZnS target is not less than 99.99%, the diameter is 60-80 mm, and the thickness is 5-6 mm.

[0025] Furthermore, the content of H2S gas in the mixed gas of H2S and nitrogen in step S2.2 is 20-30%.

[0026] Furthermore, the exhaust purification system of the annealing furnace in step S3.1 is a HTLH-VSF6 gas recovery device.

[0027] Furthermore, a chip prepared by the method for forming a composite passivation film is provided, wherein the chip consists of a SiC substrate layer and a GaN layer, and a ZnS passivation film is sputtered on the surface of the chip by a composite process.

[0028] The beneficial effects are as follows: 1. The present invention performs magnetron sputtering on a surface pre-treated wafer to coat a ZnS passivation film to obtain a coated wafer, and then performs H2S and nitrogen mixed gas plasma treatment on the surface of the coated wafer to obtain a passivated wafer. In the process of performing H2S and nitrogen mixed gas plasma treatment on the surface of the coated wafer, the mixed gas of H2S and nitrogen generates H2S cluster ions under the action of radio frequency discharge of the magnetron sputtering instrument. The H2S cluster ions generated at this time provide abundant S ions to fill S ions at S vacancies in the ZnS film, passivate S dangling bonds, thereby reducing defects and stress of the film, improving the crystallinity of the ZnS film, enhancing the stability and uniform density of the film, and H ions can adjust the charge distribution on the surface of the film, further promote the filling and passivation effect of S ions, reduce non-radiative recombination centers of the ZnS film, avoid the problems of microcracks, microdefects and film layer peeling in the passivation film, and improve the reliability of the chip.

[0029] 2. The present invention performs surface treatment by placing the clean wafer in an α-pinene vapor atmosphere. α-pinene is an organic molecule with a strong π conjugated system. This π conjugated system enables α-pinene to have a high electron-hole adsorption capacity and conductivity. Therefore, it can interact with the electrons on the surface of the clean wafer, effectively improve the energy level of the wafer surface, increase the surface energy, and form a stable charge transfer state, thereby increasing the activity of the clean wafer surface, providing energy for the ZnS particles in the subsequent magnetron sputtering process, so that it forms a more dense and uniform ZnS film, and improves the stability of the film.

[0030] 3. The present invention anneals the passivated wafer in a sulfur hexafluoride atmosphere, and the high-temperature treatment can enlarge the grain size of ZnS, which can not only further reduce defects and film stress in the sputtering process, but also the sulfur hexafluoride can further passivate the Zn dangling bonds and S dangling bonds, greatly improving the density, uniformity and stability of the film, and further improving its withstand voltage and low leakage characteristics. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The present invention is a flow chart of a method for forming a composite passivation film according to an embodiment of the present invention. DETAILED DESCRIPTION

[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Embodiment 1: A method for forming a composite passivation film and a chip comprising the passivation film, such as Figure 1 As shown, the following steps are included:

[0034] S1: Pretreatment of semiconductor wafer surface

[0035] S1.1: Immerse the GaN semiconductor wafer in an acetone solution, then place it in an ultrasonic cleaning machine, perform ultrasonic cleaning at an ultrasonic frequency of 20 kHz for 8 minutes, take it out and rinse it twice with deionized water, then immerse it in an isopropanol solution, perform ultrasonic cleaning at an ultrasonic frequency of 20 kHz for 8 minutes, take it out and continue to rinse it with deionized water twice, then immerse it in a 25% HF solution and perform ultrasonic cleaning at an ultrasonic frequency of 15 kHz for 2 minutes, take it out and rinse it with deionized water 4 times, and blow it dry with nitrogen to obtain a clean wafer;

[0036] S1.2: Place the clean wafer on the sample rack of the steam-heated reactor. The steam-heated reactor is equipped with a sample rack and a constant temperature heating table. The sample rack is arranged in a parallel bar configuration. The wall of the steam-heated reactor is connected to a vacuum pump. Place α-pinene with a volume of 1 / 20 of the steam-heated reactor on the constant temperature heating table. Then, introduce nitrogen into the steam-heated reactor so that the nitrogen content accounts for 85% of the gas content in the steam-heated reactor and the rest is air. After sealing the steam-heated reactor, start the vacuum pump, pump the air pressure in the reactor to 400 Torr, heat the temperature in the reactor to 80°C, then start the constant temperature heating table, heat the α-pinene to 85°C, and after all the α-pinene in the constant temperature heating table is evaporated, turn off the constant temperature heating table and maintain the temperature in the reactor for 10 minutes. Then turn off the heating device to obtain a surface pretreated wafer. Take out the surface pretreated wafer and cool it to room temperature under a nitrogen flow. Then, immediately transfer it to the sputtering chamber of the magnetron sputtering instrument to prepare for magnetron sputtering.

[0037] S2: Magnetron sputtering and plasma treatment of ZnS passivation film

[0038] S2.1: Install the ZnS target material on the target position of the magnetron sputtering instrument. The purity of the ZnS target material is 99.99%, the diameter is 60 mm, and the thickness is 5 mm. The surface pre-treated wafer prepared in step S1.2 is installed in the sputtering chamber of the magnetron sputtering instrument. The sputtering chamber is evacuated to a vacuum, and the vacuum degree is controlled at 10 -5 Pa, then introduce Ar gas with a purity of 99.999%, adjust the working gas pressure to 0.5 Pa, set the Ar gas flow rate to 25 sccm, then start the magnetron sputtering instrument, set the RF power to 150 W for magnetron sputtering, and plate a ZnS passivation film on the surface of the surface pretreated wafer, and control the thickness of the ZnS passivation film to 300 nm to obtain a coated wafer;

[0039] S2.2: Adjust the vacuum degree in the sputtering chamber of the magnetron sputtering instrument to 2×10 -3 Pa, the introduction of Ar gas was changed to a mixed gas of H2S and nitrogen, the content of H2S gas was 20%, the working gas pressure was adjusted to 3Pa, the gas flow rate of the mixed gas of H2S and nitrogen was adjusted to 10sccm, the magnetron sputtering instrument was started, the RF power was set to 80W, and the surface of the coated wafer was treated with a mixed gas plasma of H2S and nitrogen for 4 minutes to obtain a passivated wafer.

[0040] S3: Sulfur hexafluoride atmosphere assisted passivation wafer annealing

[0041] S3.1: Place the passivated wafer in an annealing furnace, which is connected to a HTLH-VSF6 gas recovery device, and exhaust the gas with nitrogen for 6 minutes, then introduce sulfur hexafluoride gas, control the sulfur hexafluoride gas flow rate to 10 sccm, control the heating rate in the annealing furnace to 8°C / min, slowly heat to 280°C, and then maintain the temperature and gas flow rate for 45 minutes to obtain an annealed wafer;

[0042] S3.2: After the annealing is completed, stop the sulfur hexafluoride gas supply, exhaust with nitrogen for 10 minutes, discharge the residual gas in the furnace and ensure that the exhaust gas passes through the HTLH-VSF6 gas recovery device, then take out the annealed wafer and store it in a dry environment.

[0043] Embodiment 2: A method for forming a composite passivation film and a chip comprising the passivation film, such as Figure 1 As shown, the following steps are included:

[0044] S1: Pretreatment of semiconductor wafer surface

[0045] S1.1: Immerse the GaN semiconductor wafer in an acetone solution, then place it in an ultrasonic cleaning machine, perform ultrasonic cleaning at an ultrasonic frequency of 20 kHz for 8 minutes, take it out and rinse it twice with deionized water, then immerse it in an isopropanol solution, perform ultrasonic cleaning at an ultrasonic frequency of 20 kHz for 8 minutes, take it out and continue to rinse it with deionized water twice, then immerse it in a 30% HF solution and perform ultrasonic cleaning at an ultrasonic frequency of 15 kHz for 2 minutes, take it out and rinse it with deionized water 4 times, and blow it dry with nitrogen to obtain a clean wafer;

[0046] S1.2: Place the clean wafer on the sample rack of the steam-heated reactor. The steam-heated reactor is equipped with a sample rack and a constant temperature heating table. The sample rack is arranged in a parallel bar configuration. The wall of the steam-heated reactor is connected to a vacuum pump. Place α-pinene with a volume of 1 / 15 of the steam-heated reactor on the constant temperature heating table. Then, introduce nitrogen into the steam-heated reactor so that the nitrogen content accounts for 90% of the gas content in the steam-heated reactor and the rest is air. After sealing the steam-heated reactor, start the vacuum pump, pump the air pressure in the reactor to 400 Torr, heat the temperature in the reactor to 80°C, then start the constant temperature heating table, heat the α-pinene to 85°C, and after all the α-pinene in the constant temperature heating table is evaporated, turn off the constant temperature heating table and maintain the temperature in the reactor for 10 minutes. Then turn off the heating device to obtain a surface pretreated wafer. Take out the surface pretreated wafer and cool it to room temperature under a nitrogen flow. Then, immediately transfer it to the sputtering chamber of the magnetron sputtering instrument to prepare for magnetron sputtering.

[0047] S2: Magnetron sputtering and plasma treatment of ZnS passivation film

[0048] S2.1: Install the ZnS target material on the target position of the magnetron sputtering instrument. The purity of the ZnS target material is 99.99%, the diameter is 80 mm, and the thickness is 6 mm. The surface pre-treated wafer prepared in step S1.2 is installed in the sputtering chamber of the magnetron sputtering instrument. The sputtering chamber is evacuated to a vacuum, and the vacuum degree is controlled at 10 -5 Pa, then introduce Ar gas with a purity of 99.999%, adjust the working gas pressure to 0.5 Pa, set the Ar gas flow rate to 30 sccm, then start the magnetron sputtering instrument, set the RF power to 150 W for magnetron sputtering, and plate a ZnS passivation film on the surface of the surface pretreated wafer. The thickness of the ZnS passivation film is controlled at 500 nm to obtain a coated wafer;

[0049] S2.2: Adjust the vacuum degree in the sputtering chamber of the magnetron sputtering instrument to 2×10 -3 Pa, the introduction of Ar gas was changed to a mixed gas of H2S and nitrogen, the content of H2S gas was 30%, the working gas pressure was adjusted to 3Pa, the gas flow rate of the mixed gas of H2S and nitrogen was adjusted to 15sccm, the magnetron sputtering instrument was started, the RF power was set to 80W, and the surface of the coated wafer was treated with a mixed gas plasma of H2S and nitrogen for 4 minutes to obtain a passivated wafer.

[0050] S3: Sulfur hexafluoride atmosphere assisted passivation wafer annealing

[0051] S3.1: Place the passivated wafer in an annealing furnace, which is connected to a HTLH-VSF6 gas recovery device, and exhaust the gas with nitrogen for 6 minutes, then introduce sulfur hexafluoride gas, control the sulfur hexafluoride gas flow rate to 30 sccm, control the heating rate in the annealing furnace to 8°C / min, slowly heat it to 280°C, and then maintain the temperature and gas flow rate for 45 minutes to obtain an annealed wafer;

[0052] S3.2: After the annealing is completed, stop the sulfur hexafluoride gas supply, exhaust with nitrogen for 10 minutes, discharge the residual gas in the furnace and ensure that the exhaust gas passes through the HTLH-VSF6 gas recovery device, then take out the annealed wafer and store it in a dry environment.

[0053] Embodiment 3: A method for forming a composite passivation film and a chip comprising the passivation film, such as Figure 1 As shown, the following steps are included:

[0054] S1: Pretreatment of semiconductor wafer surface

[0055] S1.1: Immerse the GaN semiconductor wafer in an acetone solution, then place it in an ultrasonic cleaning machine, perform ultrasonic cleaning at an ultrasonic frequency of 25kHz for 10 minutes, take it out and rinse it with deionized water for 3 times, then immerse it in an isopropanol solution, perform ultrasonic cleaning at an ultrasonic frequency of 25kHz for 10 minutes, take it out and continue to rinse it with deionized water for 3 times, then immerse it in a 25% HF solution and perform ultrasonic cleaning at an ultrasonic frequency of 20kHz for 2.5 minutes, take it out and rinse it with deionized water for 5 times, and blow it dry with nitrogen to obtain a clean wafer;

[0056] S1.2: Place the clean wafer on the sample rack of the steam-heated reactor. The steam-heated reactor is equipped with a sample rack and a constant temperature heating table. The sample rack is arranged in a parallel bar configuration. The wall of the steam-heated reactor is connected to a vacuum pump. Place α-pinene with a volume of 1 / 20 of the steam-heated reactor on the constant temperature heating table. Then, introduce nitrogen into the steam-heated reactor so that the nitrogen content accounts for 85% of the gas content in the steam-heated reactor and the rest is air. After sealing the steam-heated reactor, start the vacuum pump, pump the air pressure in the reactor to 500 Torr, heat the temperature in the reactor to 85°C, then start the constant temperature heating table, heat the α-pinene to 90°C, and after all the α-pinene in the constant temperature heating table is evaporated, turn off the constant temperature heating table and maintain the temperature in the reactor for 15 minutes. Then turn off the heating device to obtain a surface pretreated wafer. Take out the surface pretreated wafer and cool it to room temperature under a nitrogen flow. Then, immediately transfer it to the sputtering chamber of the magnetron sputtering instrument to prepare for magnetron sputtering.

[0057] S2: Magnetron sputtering and plasma treatment of ZnS passivation film

[0058] S2.1: Install the ZnS target material on the target position of the magnetron sputtering instrument. The purity of the ZnS target material is 99.99%, the diameter is 60 mm, and the thickness is 5 mm. The surface pre-treated wafer prepared in step S1.2 is installed in the sputtering chamber of the magnetron sputtering instrument. The sputtering chamber is evacuated to a vacuum, and the vacuum degree is controlled at 10 -4 Pa, then introduce Ar gas with a purity of 99.999%, adjust the working gas pressure to 1 Pa, set the Ar gas flow rate to 30 sccm, then start the magnetron sputtering instrument, set the RF power to 200 W for magnetron sputtering, and plate a ZnS passivation film on the surface of the surface pretreated wafer. The thickness of the ZnS passivation film is controlled at 300 nm to obtain a coated wafer;

[0059] S2.2: Adjust the vacuum degree in the sputtering chamber of the magnetron sputtering instrument to 8×10 -3 Pa, the introduction of Ar gas was changed to a mixed gas of H2S and nitrogen, the content of H2S gas was 20%, the working gas pressure was adjusted to 5Pa, the gas flow rate of the mixed gas of H2S and nitrogen was adjusted to 10sccm, the magnetron sputtering instrument was started, the RF power was set to 100W, and the surface of the coated wafer was treated with a mixed gas plasma of H2S and nitrogen for 5 minutes to obtain a passivated wafer.

[0060] S3: Sulfur hexafluoride atmosphere assisted passivation wafer annealing

[0061] S3.1: Place the passivated wafer in an annealing furnace, which is connected to a HTLH-VSF6 gas recovery device. First, exhaust the gas with nitrogen for 8 minutes, then introduce sulfur hexafluoride gas, control the sulfur hexafluoride gas flow rate to 10 sccm, control the heating rate in the annealing furnace to 10°C / min, slowly heat to 300°C, and then maintain the temperature and gas flow rate for 60 minutes to obtain an annealed wafer;

[0062] S3.2: After the annealing is completed, stop the sulfur hexafluoride gas supply, exhaust with nitrogen for 15 minutes, discharge the residual gas in the furnace and ensure that the exhaust gas passes through the HTLH-VSF6 gas recovery device, then take out the annealed wafer and store it in a dry environment.

[0063] Comparative Example 1: The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 removes step S2.2 and replaces the subsequent passivation wafer with a coated wafer. The remaining steps are the same as Example 1 to obtain an annealed wafer, which is recorded as Comparative Example 1.

[0064] Comparative Example 2: The difference between Comparative Example 2 and Example 1 is that step S1.2 is removed in Comparative Example 2, and the remaining steps are the same as those in Example 1, to produce an annealed wafer, which is recorded as Comparative Example 2.

[0065] Comparative Example 3: The difference between Comparative Example 3 and Example 1 is that in Comparative Example 3, sulfur hexafluoride gas is not introduced during the annealing process in step S3.1, and the remaining steps are the same as those in Example 1, to obtain an annealed wafer, which is recorded as Comparative Example 3.

[0066] Experiment 1: Take the annealed wafers prepared in Example 1 and Comparative Examples 1-3, select a circular area with a diameter of 80 mm and select 84 sampling points to test the thickness of the ZnS film using the ellipsometry method, and calculate the film thickness uniformity d = (d max -d min ) / d 平均 ×100%,d max d min are the maximum and minimum film thickness of the annealed wafer, respectively; d 平均 The average film thickness of all annealed wafers was recorded and tabulated, as shown in Table 1. It can be seen that the film thickness uniformity of the annealed wafer prepared in Example 1 is greater than the film thickness uniformity of Comparative Examples 1-3, which can prove that the mixed gas plasma treatment of H2S and nitrogen on the surface of the coated wafer can improve the uniformity of the ZnS film. At the same time, it can be proved that placing the clean wafer in an α-pinene vapor atmosphere for surface treatment can also improve the uniformity of the ZnS film. It can also be proved that placing the passivated wafer in a sulfur hexafluoride atmosphere for annealing can improve the uniformity of the ZnS film.

[0067] Table 1: Uniformity of annealed wafer films

[0068]

[0069] Experiment 2: Take the annealed wafers prepared in Examples 1-3 and Comparative Examples 1-3, use the X-ray reflection method to measure the reflection intensity of the film, deduce the relationship between the film density and the critical angle according to the Fresnel refraction law, and use the fitting method to calculate the density of the film. The test and calculation are performed three times respectively, and the data are recorded and tabulated. As shown in Table 2, it can be seen that the film density of the annealed wafers prepared in Examples 1-3 is greater than the film density of Comparative Examples 1-3, which can prove that the mixed gas plasma treatment of H2S and nitrogen on the surface of the coated wafer can improve the density of the ZnS film. At the same time, it can be proved that placing the clean wafer in an α-pinene vapor atmosphere for surface treatment can also improve the density of the ZnS film. It can also be proved that placing the passivated wafer in a sulfur hexafluoride atmosphere for annealing can improve the density of the ZnS film.

[0070] Table 2: Density of annealed wafer films

[0071]

[0072] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A method for forming a composite passivation film, characterized in that: The following steps are involved: S1: Pretreatment of semiconductor wafer surface The GaN semiconductor wafer is sequentially immersed in an acetone solution, an isopropanol solution and an HF solution for ultrasonic cleaning, and is rinsed with deionized water after each ultrasonic cleaning. After drying with nitrogen, a clean wafer is obtained, and the clean wafer is placed in a closed steam heating reactor, and α-pinene is heated by a constant temperature heating table to evaporate in the steam heating reactor. After the α-pinene is completely evaporated, the temperature in the reactor is maintained to obtain a surface pre-treated wafer, and the surface pre-treated wafer is taken out and placed under a nitrogen flow for cooling, and then immediately transferred to a sputtering chamber of a magnetron sputtering instrument to prepare for magnetron sputtering; S2: Magnetron sputtering and plasma treatment of ZnS passivation film The ZnS target material is installed on the target position of a magnetron sputtering instrument, a surface pre-treated wafer is installed in the sputtering chamber of the magnetron sputtering instrument, Ar gas is introduced, a ZnS passivation film is plated on the surface of the surface pre-treated wafer, and a coated wafer is obtained, then the Ar gas is changed to a mixed gas of H2S and nitrogen, the working gas pressure and the gas flow rate of the mixed gas of H2S and nitrogen are adjusted, and the magnetron sputtering instrument is started to perform a mixed gas plasma treatment of H2S and nitrogen on the surface of the coated wafer to obtain a passivated wafer; S3: Sulfur hexafluoride atmosphere assisted passivation wafer annealing Place the passivated wafer in an annealing furnace, exhaust the gas with nitrogen first, then introduce sulfur hexafluoride gas, control the flow rate of sulfur hexafluoride gas, slowly increase the temperature and maintain the temperature and gas flow rate for annealing to obtain an annealed wafer. After the annealing is completed, stop the sulfur hexafluoride gas supply, exhaust the gas with nitrogen, discharge the residual gas in the furnace and ensure that the waste gas passes through the exhaust purification system, then take out the annealed wafer and store it in a dry environment.

2. The method for forming a composite passivation film according to claim 1, characterized in that: Step S1: Pretreatment of the surface of the semiconductor wafer, including the following steps: S1.1: Immerse the GaN semiconductor wafer in an acetone solution, then place it in an ultrasonic cleaning machine, perform ultrasonic cleaning at an ultrasonic frequency of 20-25kHz for 8-10 minutes, take it out and rinse it with deionized water for 2-3 times, then immerse it in an isopropanol solution, perform ultrasonic cleaning at an ultrasonic frequency of 20-25kHz for 8-10 minutes, take it out and continue to rinse it with deionized water for 2-3 times, then immerse it in a HF solution with a concentration of 25-30% and perform ultrasonic cleaning at an ultrasonic frequency of 15-20kHz for 2-2.5 minutes, take it out and rinse it with deionized water for 4-5 times, blow it dry with nitrogen to obtain a clean wafer; S1.2: Place the clean wafer on the sample rack of the steam-heated reactor, place α-pinene on a constant temperature heating table, and then introduce nitrogen into the steam-heated reactor so that the nitrogen content accounts for 85-90% of the gas content in the steam-heated reactor, and the rest is air. After sealing the steam-heated reactor, start the vacuum pump to evacuate the air pressure in the reactor to 400-500Torr, and heat the temperature in the reactor to 80-85°C. Then start the constant temperature heating table to heat α-pinene to 85-90°C. After all the α-pinene in the constant temperature heating table is evaporated, turn off the constant temperature heating table and maintain the temperature in the reactor for 10-15 minutes, then turn off the heating device to obtain a surface pretreated wafer, take out the surface pretreated wafer, cool it to room temperature under a nitrogen flow, and then immediately transfer it to the sputtering chamber of the magnetron sputtering instrument to prepare for magnetron sputtering.

3. The method for forming a composite passivation film according to claim 2, characterized in that: Step S2: magnetron sputtering and plasma treatment of the ZnS passivation film, comprising the following steps: S2.1: Install the ZnS target material on the target position of the magnetron sputtering instrument. The surface pre-treated wafer prepared in step S1.2 is installed in the sputtering chamber of the magnetron sputtering instrument. The sputtering chamber is evacuated to a vacuum with the vacuum degree controlled at 10 -5 -10 -4 Pa, then introduce Ar gas with a purity greater than 99.999%, adjust the working gas pressure to 0.5-1Pa, set the Ar gas flow rate to 25-30sccm, then start the magnetron sputtering instrument, set the RF power to 150-200W for magnetron sputtering, and plate a ZnS passivation film on the surface of the surface pretreated wafer, and control the thickness of the ZnS passivation film to be 300-500nm to obtain a coated wafer; S2.2: Adjust the vacuum degree in the sputtering chamber of the magnetron sputtering instrument to 2×10 -3 -8×10 -3 Pa, the introduction of Ar gas is changed to the introduction of a mixed gas of H2S and nitrogen, the working gas pressure is adjusted to 3-5Pa, the gas flow rate of the mixed gas of H2S and nitrogen is adjusted to 10-15sccm, the magnetron sputtering instrument is started, the RF power is set to 80-100W, and the surface of the coated wafer is treated with a mixed gas plasma of H2S and nitrogen for 4-5 minutes to obtain a passivated wafer.

4. The method for forming a composite passivation film according to claim 3, characterized in that: Step S3: annealing the passivated wafer in a sulfur hexafluoride atmosphere, comprising the following steps: S3.1: Place the passivated wafer in an annealing furnace, which is connected to an exhaust purification system. First, exhaust the gas with nitrogen for 6-8 minutes, then introduce sulfur hexafluoride gas, control the sulfur hexafluoride gas flow rate to 10-30 sccm, control the heating rate in the annealing furnace to 8-10°C / min, slowly heat to 280-300°C, and then maintain the temperature and gas flow rate for 45-60 minutes to obtain an annealed wafer; S3.2: After the annealing is completed, stop the sulfur hexafluoride gas supply, exhaust with nitrogen for 10-15 minutes, discharge the residual gas in the furnace and ensure that the exhaust gas passes through the exhaust purification system, then take out the annealed wafer and store it in a dry environment.

5. The method for forming a composite passivation film according to claim 2, characterized in that: The steam-heated reactor in step S1.2 is equipped with a sample rack and a constant temperature heating table. The sample rack is arranged in a double-bar configuration, and the wall of the steam-heated reactor is connected to a vacuum pump.

6. The method for forming a composite passivation film according to claim 2, characterized in that: The amount of α-pinene added in step S1.2 is 1 / 20-1 / 15 of the volume of the steam-heated reactor.

7. The method for forming a composite passivation film according to claim 3, characterized in that: In step S2.1, the purity of the ZnS target is not less than 99.99%, the diameter is 60-80 mm, and the thickness is 5-6 mm.

8. The method for forming a composite passivation film according to claim 3, characterized in that: The content of H2S gas in the mixed gas of H2S and nitrogen in step S2.2 is 20-30%.

9. The method for forming a composite passivation film according to claim 4, characterized in that: Step S3.1 The exhaust purification system of the annealing furnace is a HTLH-VSF6 gas recovery device.

10. A chip prepared according to the method for forming a composite passivation film according to any one of claims 1 to 9, characterized in that The chip consists of a SiC substrate layer and a GaN layer, and a ZnS passivation film is sputtered on the surface of the chip through a composite process.